Association between neighborhood deprivation and type 2 diabetes risk among ADHD patients: a nationwide population-based cohort study - Li, Yiman; Yang, Huifang; Sundquist, Kristina; Sundquist, Jan; Zhang, Yuhong; Li, Xinjun (Frontiers in Public Health, 2025)
ObjectiveBoth attention-deficit/hyperactivity disorder (ADHD) and neighborhood deprivation have been previously associated with an increased risk of type 2 diabetes (T2D). However, the potential association between neighborhood deprivation and T2D in ADHD patients remains underexplored. Our aim was to study the potential effect of neighborhood deprivation on incident T2D in patients with ADHD.MethodsThis study included adults (n = 246,515) with ADHD who were followed in Sweden from 2001 to 2018 for incident T2D. The relationship between neighborhood deprivation and incident T2D was examined using Cox regression analysis, reporting hazard ratios (HRs) with 95% confidence intervals (CIs). All models were stratified by sex and adjusted for age, educational level, family income, employment status, region of residence, immigrant status, marital status, family history of T2D, and comorbidities. Patients with ADHD residing in neighborhoods with high or moderate deprivation were compared to those in neighborhoods with low deprivation (reference group).ResultsA significant association was observed between neighborhood deprivation and T2D in patients with ADHD. Among patients with ADHD residing in highly deprived neighborhoods, the HRs were 1.37 (95% CI: 1.22–1.53) for men and 1.84 (95% CI: 1.61–2.12) for women, compared to those in low-deprivation neighborhoods. After adjusting for potential confounders, the association remained significant, with HRs of 1.19 (95% CI: 1.06–1.34) in men and 1.48 (95% CI: 1.28–1.70) in women residing in highly deprived neighborhoods.ConclusionThe increased incidence of T2D among patients with ADHD residing in deprived neighborhoods raises significant clinical and public health concerns. These findings could assist policymakers in allocating resources within primary healthcare settings and provide guidance for clinicians working with patients in deprived neighborhoods.